New approach to hydrosilylation reaction in ionic liquids as solvent in microreactor system. Issue 66 (29th June 2016) - Kukawka, R.; Pawlowska-Zygarowicz, A.; Dutkiewicz, M.; Maciejewski, H.; Smiglak, M.
Abstract : Continuous flow-through reactors on a micro scale (microreactors) are being investigated as a new approach to chemical synthesis, due to larger surface-to-volume ratios and micro-structured internal volumes, which allow for efficient heat exchange. Abstract : Continuous flow-through reactors on a micro scale (microreactors) are being investigated as a new approach to chemical synthesis, due to significantly larger surface-to-volume ratios and micro-structured internal volumes, which allow for much more efficient heat exchange. Functionalized siloxanes, as one of the most important classes of organosilicon compounds, are widely applied in industry. Many of their synthetic methods are based on the catalytic process of hydrosilylation. In our studies, we investigated, as a model, the reaction between 1, 1, 1, 3, 5, 5, 5-heptamethyltrisiloxane and 1-octene, using the Karstedt catalyst dissolved in seven different ionic liquids. The reaction was carried out in batch and in the microreactor system. Studies have shown that the use of ionic liquids in general allows for catalyst recycling and reuse in subsequent reaction cycles. Moreover, the use of microreactors intensified the process, allowing a higher yield to be obtained than when using conventional batch reactions.